Promoting mental health in higher education: towards a model of well-being factors in emerging adulthood - Ariadna Martínez-García; Susana Valverde-Montesino; Mercedes García-García (International Journal of Qualitative Studies on Health & Well-Being)
Purpose This study aims to contribute to the development of a theoretical model that is useful for enhancing well-being/positive mental health with pedagogical resources that enable the acquisition of skills and knowledge, particularly during Emerging Adulthood. Methods This paper enquires into the role of well-being promotion in higher education following the dual-factor model of mental health difficulties and wellbeing. The study narratively reviews the main well-being models and presents a compared theoretical synthesis examining the dimensions that promote or facilitate the presence of well-being using a promotion approach. Results The study identifies 14 dimensions involved in wellbeing—emotional, psychological and social factors—that can be potentially improved through learning processes. Drawing on empirical and theoretical studies on emerging adult population, a factorial model is proposed. Preliminary factor interactions are examined paying close attention to the cognitive processes that explain or affect their relationship with well-being, the possible correlations between them and particularities of emerging adults. Conclusion Wellbeing factors can be particularly targeted by educational promotion, as they can be developed through learning processes. An integrative model that provides a broad perspective can assist in pedagogical design and defining educational goals for these learning processes involved in wellbeing promotion.